Pengaruh Kualitas Produk, Influencer Marketing dan Fomo terhadap Keputusan Pembelian Madmilk Japanese Bakery - Nadira Assyifa; Darwin Raja Unggul Saragih (Indonesian Journal Publisher, 2025)
This study aims to analyze the influence of product quality, influencer marketing, and the phenomenon of Fear of Missing Out (FOMO) on purchase decisions among consumers of Madmilk Japanese Bakery in the city of Casablanca. The research employs a quantitative approach with a survey method, involving 122 respondents selected using purposive sampling techniques. Data collection instruments utilized a questionnaire with a five-point Likert scale. Data analysis was conducted through classical assumption tests (normality, heteroscedasticity, autocorrelation, multicollinearity, and linearity) and multiple linear regression analysis to test the research hypotheses. The results indicate that product quality, influencer marketing, and FOMO significantly and positively affect consumer purchase decisions. These findings underscore the importance of strategies to enhance product quality, implement effective influencer marketing, and manage FOMO phenomena to increase purchase decisions in the food and beverage industry. The implications of this study suggest that business practitioners can adopt these findings to develop more effective marketing strategies that enhance consumer appeal and loyalty in today’s digital era.